Analisis Dan Perancangan Aplikasi Kasir Toko Kelontong ABC Berbasis Website Menggunakan Metode Waterfall - Riska Suryani; Retno Agus Setiawan (Universitas Al-Irsyad Cilacap, 2026)
The advancement of information technology has opened up opportunities for small businesses, including traditional retail stores (toko kelontong), to improve efficiency and service quality. However, many of these stores in Indonesia still rely on manual systems, which cause various issues in managing transactions, inventory, and sales reporting. This study aims to design and evaluate a web-based cashier application intended to modernize the operations of toko kelontong. The application was developed using the Waterfall method, consisting of requirements analysis, system design, implementation, testing, and maintenance. The implementation results show that the application successfully accommodates essential functions such as transaction recording, inventory management, receipt printing, and structured sales reporting. Black Box testing confirmed that all core features functioned correctly without errors, while a usability evaluation using the System Usability Scale (SUS) yielded an average score of 72.5, categorized as “good.” These findings indicate that the web-based cashier application is not only effective in enhancing operational efficiency but also offers a high level of user comfort and ease of use, making it a promising digital solution for traditional stores to remain competitive in the digital era.